Extended study of extreme geoelectric field event scenarios for geomagnetically induced current applications. Issue 3 (29th March 2013) - Ngwira, Chigomezyo M.; Pulkkinen, Antti; Wilder, Frederick D.; Crowley, Geoffrey
Abstract : [1] Geomagnetically induced currents (GIC) flowing in man‐made ground technological systems are a direct manifestation of adverse space weather. Today, there is great concern over possible geomagnetically induced current effects on power transmission networks that can result from extreme space weather events. The threat of severe societal consequences has accelerated recent interest in extreme geomagnetic storm impacts on high‐voltage power transmission systems. As a result, extreme geomagnetic event characterization is of fundamental importance for quantifying the technological impacts and societal consequences of extreme space weather. This article reports on the global behavior of the horizontal geomagnetic field and the induced geoelectric field fluctuations during severe/extreme geomagnetic events. This includes (1) an investigation of the latitude threshold boundary, (2) the local time dependency of the maximum induced geoelectric field, and (3) the influence of the equatorial electrojet (EEJ) current on the occurrence of enhanced induced geoelectric fields over ground stations located near the dip equator. Using ground‐based and satellite‐borne Defense Meteorological Satellite Program measurements, this article confirms that the latitude threshold boundary is associated with the movements of the auroral oval and the corresponding auroral electrojet current system, which is the main driver of the largest perturbations of the ground geomagnetic field at high latitudes. In addition, we show that the enhancement of the EEJ is driven by the penetration of high‐latitude electric fields and that the induced geoelectric fields at stations within the EEJ belt can be an order of magnitude larger than that at stations outside the belt. This has important implications for power networks located around the electrojet belt and confirms that earlier observations by Pulkkinen et al. (2012) were not isolated incidences but rather cases that can occur during certain severe geomagnetic storm events. Key Points: This study confirms threshold boundary associated with movements of auroral current system. This study shows that the enhancement of the EEJ is driven by penetration electric fields. This study presents important implications for power networks located around the EEJ belt.